Improving students' performance via case-based e-learning - Ertl, Sebastian; Wadowski, Patricia P.; Löffler-Stastka, Henriette (Frontiers in Medicine, 2025)
BackgroundThe integration of interdisciplinary clinical reasoning and decision-making into the medical curriculum is imperative. Novel, high-quality e-learning environments, encompassing virtual clinical and hands-on training, are essential. Consequently, we evaluated the efficacy of a case-based e-learning approach.MethodThe impact of a case-based interdisciplinary e-learning environment with an integrated question/feedback system on medical students' academic performance was examined in a cross-sectional sample of different study years, longitudinally matched per academic year. Differences between the groups were analyzed through an unpaired t-test.ResultsThe exam results of students who participated in the e-learning course (n = 296) were compared with those of all students at the university (n = 5,800). A statistically significant (p-value < 0.01) improvement in students' final examination grades was observed through intensive training on the offered platform.ConclusionsOur analyses demonstrated the positive influence of a case-based e-learning approach within the Viennese medical curriculum.